(untitled) (Economics and region, 2021)
The article was analyzed the existing conceptual approaches to the definition of “self-management”. It was found that each approach is based on separate methods and principles of management, has its advantages and disadvantages. The author’s approach to understanding self-management was offered, which allowed identifying the most relevant methods and techniques that should be used by managers in their work in conditions when managers are required to create creative ideas, innovate, adapt to quarantine, form new habits of their work and the team as well. Methods of self-development were offered for managers who want to achieve rapid career growth, have respect among others, implement their own plans and achieve their goals. The importance of self-regulation for a modern manager was proved, as well as methods of self-regulation that should be used to eliminate tension, reduce emotional stress, increase resource mobilization, reduce the possibility of apathetic moods and more.